Teater og litteratur: Et ontologisk aspekt af forholdet mellem de to - GIlyazova, Olga Serveevna; Visby, Morten (Passage - Tidsskrift for litteratur og kritik, 2025)
Theatre and Literature: An Ontological Aspect of their Relationship The analysis of a dramatic work is generally characterized by two approaches, which are frequently counter-posed to each other: The approach based on theatre studies tends to narrow down a dramatic text to a script, while the approach based on literary studies tends to see the above text without regard to its theatrical implementation. In our essay, we assume that these two approaches are intertwined: A dramatic work is meant for theatrical performance, which makes it different from other forms of literature. The theatrical nature of dramatic works leaves an imprint on their literary characteristics. We offer a new way of looking at the relationship between the performance text and the dramatic text from the ontological, semiotic, and communicative perspective.